Thrombin obliteration of subclavian artery aneurysm with intravascular balloon protection - Woźniak, Witold; Mlosek, Robert Krzysztof; Górski, Grzegorz; Myrcha, Piotr; Ciostek, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
A rare case of a 56-year-old man with posttraumatic false aneurysm of the right subclavian artery is presented. He was admitted to hospital due to pain in the shoulder. The diagnosis was made upon ultrasonography and computed tomography (CT) results. With ultrasound guidance, the aneurysm was punctured and injected with bovine thrombin (Biotrombina 400u, Biomed). During the injection, the aneurysm neck was occluded by an endovascular balloon placed in the subclavian artery. Complete aneurysm embolisation was confirmed by ultrasound and CT studies. The postoperative course was complicated by Horner’s syndrome which resolved completely within 3 weeks. The procedure technique is described in detail.